CREATIVE CLIMATE IN METHODICAL WORK AS ONE OF CONDITIONS FOR THE DEVELOPMENT OF CREATIVE STYLE ACTIVITIES OF TEACHER - Dudnichenko, N.V. (Pedagogy of Higher and Secondary Education, 2022)
There is a dependence of the development of teacher’s Creative style from the present conditions of school work. The organization of creative climate during the method work as one of the conditions is a high possibility of teacher’s positive attitude to professionalfursonal work.